If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 5y + 6z + -2x + z + -8y = 0 Reorder the terms: 5x + -2x + 5y + -8y + 6z + z = 0 Combine like terms: 5x + -2x = 3x 3x + 5y + -8y + 6z + z = 0 Combine like terms: 5y + -8y = -3y 3x + -3y + 6z + z = 0 Combine like terms: 6z + z = 7z 3x + -3y + 7z = 0 Solving 3x + -3y + 7z = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3y' to each side of the equation. 3x + -3y + 3y + 7z = 0 + 3y Combine like terms: -3y + 3y = 0 3x + 0 + 7z = 0 + 3y 3x + 7z = 0 + 3y Remove the zero: 3x + 7z = 3y Add '-7z' to each side of the equation. 3x + 7z + -7z = 3y + -7z Combine like terms: 7z + -7z = 0 3x + 0 = 3y + -7z 3x = 3y + -7z Divide each side by '3'. x = y + -2.333333333z Simplifying x = y + -2.333333333z
| 4=7(r-3) | | -36=3(x-3)-6x | | 4-5y=-20 | | 9=6(q-6) | | 0=-0.09+1.1x | | 7x-2(4x+23)+12= | | 5+7=2x | | -6(-3)-7(2)=4 | | 2(y+5)-4y=16 | | 3n-n+5= | | 5+2(2x-5)=-2+3(x-2) | | 2x-5x=-1-5 | | -4x-8=3x-17 | | 750+30x=y | | -9(a+6)=2 | | y=-3.3x-3.3 | | x+x+11=37 | | 2(2x+1)+x=-39 | | y=-2x^2-24x-20 | | -9=m-98 | | Y^2+21y=0 | | 13=-7+r | | 4x-35=25 | | -1(x+3)=2x-12 | | -3(6-5x)=27 | | -8(p-9)=6 | | 32+4n=96 | | (x*8)-(x*3)=60 | | -6.3-2.3b=26.13 | | 56x+8y=24 | | 5+7y=82 | | -3(j+4)=8 |